2012
DOI: 10.1093/rheumatology/kes261
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between autoantibody clustering and clinical subsets in SLE: cluster and association analyses in Hong Kong Chinese

Abstract: We conclude that autoantibody clustering and clinical subsets exist in SLE patients of our locality. These clusters may be viewed as a bipolar spectrum of related autoantibody and clinical manifestations. At one end are patients with over-representation of anti-dsDNA and renal disorder, while at the other end are two distinct autoantibody clusters (anti-Sm/anti-RNP/aPL and anti-Ro/anti-La) with overlapping of other clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
6
23
3
Order By: Relevance
“…In addition, the presence of anti-RNP appeared to predict an approximately 8-fold increase in the SLE flare incidence during the same follow-up period. Moreover, our results suggested that the presence of anti-RNP at diagnosis is associated a greater incidence of arthritis and rash and may significantly promote the development of arthritis, rash, and mucosal ulcers, thus contributing to SLE flare according to the SLEDAI-2K definition, a finding that was consistent with the results of a previous study [9]. On the other hand, in contrast to previously reported results, the incidence of diffuse interstitial lung disease and pulmonary arterial hypertension did not differ according to the presence of anti-RNP [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the presence of anti-RNP appeared to predict an approximately 8-fold increase in the SLE flare incidence during the same follow-up period. Moreover, our results suggested that the presence of anti-RNP at diagnosis is associated a greater incidence of arthritis and rash and may significantly promote the development of arthritis, rash, and mucosal ulcers, thus contributing to SLE flare according to the SLEDAI-2K definition, a finding that was consistent with the results of a previous study [9]. On the other hand, in contrast to previously reported results, the incidence of diffuse interstitial lung disease and pulmonary arterial hypertension did not differ according to the presence of anti-RNP [10].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we assumed that the presence of anti-Smith antibodies might be predictive of SLE flare in the early phase of disease, as all 11 patients with anti-Smith antibodies were also anti-RNP-positive. Anti-Smith antibodies and anti-RNP might be simultaneously detected at a high rate in SLE patients, as these autoantibodies were classified and analyzed in the same cluster in previous studies [9,17]. In the present study; however, anti-Smith antibodies were only detected in patients having anti-RNP, and therefore we could not distinguish the direct effect of anti-Smith antibodies from the mutual effect of both types of autoantibodies.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a recent and very large study from China, 1928 patients with SLE from five different centres were studied according to serological profiles 50. The presence of anti-dsDNA was found to be associated with renal disorder, serositis and haematological involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the detailed definition of each element was not provided in the study (63). Cluster analysis and principal analysis have been used in other autoimmune diseases to establish subgroups (64)(65)(66). Our group used data mining technique to explore subgroup clusters of MG and confirmed existence of some subgroups in the above-mentioned subgroup classifications (unpublished data).…”
Section: Subgroups Of Myasthenia Gravis (Mg)mentioning
confidence: 99%